Machine learning algorithms to predict major bleeding after isolated coronary artery bypass grafting - Gao, Yuchen; Liu, Xiaojie; Wang, Lijuan; Wang, Sudena; Yu, Yang; Ding, Yao; Wang, Jingcan; Ao, Hushan (Frontiers in Cardiovascular Medicine, 2022)
Objective Postoperative major bleeding is a common problem in patients undergoing cardiac surgery and is associated with poor outcomes. We evaluated the performance of machine learning (ML) methods to predict postoperative major bleeding. Methods A total of 1045 patients who underwent isolated coronary artery bypass graft surgery (CABG) were enrolled. Their datasets were assigned randomly to a training (70%) or a testing set (30%). The primary outcome was major bleeding defined as the universal definition of peri-operative bleeding (UDPB) class 3-4. We constructed a reference logistic regression model using known predictors. We also developed several modern machine learning algorithms. In the test set, we compared the area under the receiver operating characteristic curves (AUCs) of these machine learning algorithms with the reference logistic regression model results, and the TRUST and WILL-BLEED risk score. Calibration analysis was undertaken using the calibration belt method. Results The prevalence of postoperative major bleeding was 7.1% (74/1045). For major bleeds, the conditional inference random forest model showed the highest AUC (0.831[0.732-0.930]), and the stochastic gradient boosting and random forest models demonstrated the next best results (0.820[0.742-0.899], 0.810[0.719-0.902]). The AUCs of all machine learning models were higher than 0.629 [0.517-0.641], 0.557 [0.449-0.665], as achieved by TRUST and WILL-BLEED, respectively. Conclusions Machine learning methods successfully established predicted major bleeding after cardiac surgery, with greater performance compared with previous scoring models. Modern machine learning models may enhance identification of high-risk major bleeding subpopulations.